2009
DOI: 10.1038/leu.2008.397
|View full text |Cite
|
Sign up to set email alerts
|

The DNA methyltransferase inhibitors azacitidine, decitabine and zebularine exert differential effects on cancer gene expression in acute myeloid leukemia cells

Abstract: The three DNA methyltransferase (DNMT)-inhibiting cytosine nucleoside analogues, azacitidine, decitabine and zebularine, which are currently studied as nonintensive therapy for myelodysplastic syndromes and acute myeloid leukemia (AML), differ in structure and metabolism, suggesting that they may have differential molecular activity. We investigated cellular and molecular effects of the three substances relative to cytarabine in Kasumi-1 AML blasts. Under in vitro conditions mimicking those used in clinical tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
229
3
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 296 publications
(250 citation statements)
references
References 39 publications
15
229
3
3
Order By: Relevance
“…Of course, the primary mechanism(s) by which the hypomethylating agents mediate their activity in MDS and AML in vivo is a matter of debate, and beyond the in vivo DNA demethylation of several genes, 27,29,30 DNA damage has also been shown. [31][32][33] Although at least part of the activity of 5-azacytidine in the setting may be a 'debulking' effect on the leukemic population, it is notable in this context that no treatment-related leukopenia was seen in two of the patients attaining CR subsequent to repeated courses of 5-azacytidine and DLI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of course, the primary mechanism(s) by which the hypomethylating agents mediate their activity in MDS and AML in vivo is a matter of debate, and beyond the in vivo DNA demethylation of several genes, 27,29,30 DNA damage has also been shown. [31][32][33] Although at least part of the activity of 5-azacytidine in the setting may be a 'debulking' effect on the leukemic population, it is notable in this context that no treatment-related leukopenia was seen in two of the patients attaining CR subsequent to repeated courses of 5-azacytidine and DLI.…”
Section: Discussionmentioning
confidence: 99%
“…This effect would be unique to drugs with epigenetic activity, as LD-AraC has no DNA methyltransferase inhibitor activity 26 and, when compared with DNA demethylating agents, does not reinduce genes. 27 In an attempt to improve the outcome of AML/MDS patients eligible for DLI, pretreatment with 5-azacytidine was initiated at a total dose per course of 300 mg (which is less than one-third of the FDA-approved dose of 525 mg/m 2 per treatment course), and, with a 3-day schedule, less than half of the 7-day drug exposure time of that schedule. The rationale for administering DLI 10 days after the first dose of 5-azacytidine in a given treatment cycle was to allow for maximum induction of cancer testis Ag expression, based on in vitro data showing a time-dependent upregulation of these proteins until at least day 6, with subsequent decrease at day 21.…”
Section: Discussionmentioning
confidence: 99%
“…AZA administration and toxicity AZA was administered for a median of three cycles (range, [1][2][3][4][5][6][7][8][9][10][11][12], at a dose of 75 mg/m 2 per day for 7 days every 4 weeks for the majority of the patients (92%). AZA dose was reduced to 60 mg/m 2 per day (two patients) for 7 days according to the attending physician because of fear of toxicity.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…9 AZA has been shown to increase the expression of tumor Ags by leukemic cells. [10][11][12][13] AZA can also increase regulatory T cells and CD8 þ tumor-specific T-cell responses both in vitro and in the human clinical setting. 14,15 Thus, AZA administration may potentially enhance the GVL effect while reducing active GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…At lower doses, azacitidine and decitabine have been shown to induce DNA hypomethylation. 16 However, there is currently no good evidence to suggest that this underlies their mechanism of action in patients. 17 Controlled studies of MDS using subcutaneous 5-azacitidine (75 mg/m 2 /d for 7 days every 28 days) 18 or intravenous decitabine (15 mg/m 2 over 3 hours every 8 hours for 3 days every 6 weeks) 19 have shown that the 2 drugs are associated with response rates similar to those of subcutaneous low-dose cytarabine 20 : complete remission (CR) rates of 9%, 7%, and 20.3% and partial remission rates of 8%, 16%, and 11.9%, respectively.…”
Section: Azacitidine and Decitabinementioning
confidence: 99%